Perceived barriers to the Islamic concept of sustainability - Ali, Shujahat; Reardon, Jack (Library of Sultan Agung Islamic University, 2023)
The Holy Quran and the Hadith give the principles of sustainable development, which have existed for centuries; it is not a new concept in Islamic society. But recently many social evils are arising, just because, we are neglecting these rules and principles in our daily life cycle at the level of civic society and government in the Islamic world. In the Islamic view, Allah created every supported thing in the award of human beings but give the rule of consumption without unnecessary distribution. In this research paper, data was collected through a structured interview method from 16 students. This data analysis with the tool of text analysis getting get could an image and explains in detail this collected data. And conclude some important barriers which create the hurdle in the way of establishing the concept of Islamic sustainable development.